The prevalence of self-reported chronic fatigue in a U.S. twin registry - Furberg, Helena (2005)
OBJECTIVE: To investigate the prevalence and correlates of various definitions of self-reported lifetime fatiguing illness in a U.S. twin registry. METHODS: Data from 4591 female and male twins from the population-based Mid-Atlantic Twin Registry were available for this study. Variables representing different definitions of lifetime fatiguing illness and personal characteristics were obtained through questionnaires. Odds ratios and 95% confidence intervals were calculated as measures of association between fatigue and gender. Kaplan–Meier curves were produced to examine the age at onset for lifetime fatiguing illnesses. RESULTS: Prevalences for different definitions of self-reported lifetime fatigue ranged from 36.7% for any fatigue to 2.7% for chronic fatigue syndrome-like illness. Females were two to three times more likely to report fatigue than males. Gender differences increased as fatigue definitions grew more restrictive. Ages at onset of chronic fatiguing illness were significantly earlier and the number of ancillary symptoms was greater for females than males. People with lifetime fatigue had significantly more compromised functional status than people without lifetime fatigue. CONCLUSION: The prevalence of self-reported lifetime fatiguing illness varied widely depending upon how it was defined. Given the debilitating consequences of fatiguing illnesses, the reasons for the female predominance and the earlier onset in women should receive increased research priority.